Much ado about nothing [videorecording (DVD)] - Shakespeare, William, 1564-1616; Whedon, Joss, 1964-; Shakespeare, William, 1564-1616; Fillion, Nathan, 1971-; Diamond, Reed Edward; Acker, Amy, 1976-; Gregg, Clark, 1962-; Denisof, Alexis, 1966-; Kranz, Fran, 1983- (Lionsgate, 2013)
Joss Whedon's sexy and contemporary spin on Shakespeare's classic comedy about the story of sparring lovers Beatrice and Benedick offers a sensual, tragic and occasionally absurd view of the intricate game that is love.